Student's Creativity in an Educational Environment: Revelation and Inquisitiveness - Mehrad, Aida; Mehrad, Anita (Papanda Publisher, 2023)
Revelation is one of the distinctive characteristics of a human being, which immensely contributes to its progress and success; in fact, an individual is born with the power of revelation and curiosity, which makes him strive and discover the world around him. Accordingly, inquisitive individuals are more motivated to face and solve diverse situations. Revelation and inquisitiveness are additional in individuals, showing the degree of crystallization of their creativity and innovations in different ways. Inquisitive individuals do creative things, which is a vital point for them. Consequently, it is necessary to pay attention to the environmental conditions, specifically the educational environment, and meet the requirements of individuals, particularly students from teachers and academic staff in the educational environment. It not only encourages the development of the individual but even assists the development of society. This literature focuses on the role of revelation and curiosity of students in the educational environment and in creating creativity that must be considered and supported by teachers and academic staff at educational centers. This focus can be helpful for all in charge to provide a dynamic atmosphere for the students and offer them the need to grow their creativity to have a better future and career.